Facts and Fictions: Emotional Authenticity and Narrative in Natural History Exhibitions - Jordan Kistler (Museum & Society)
This article explores the role of narrative in the generation of emotional authenticity, a feeling that something is real rather than the fact of its authenticity, arguing that the fictive (the structures of literature) can work to obscure the fictions (what is invented or untrue) at work in all museum displays. By looking at two natural history exhibitions with varying levels of cultural authority, the Natural History Museum London and the Loch Ness Centre in Scotland, this article argues for the need for literature and science to work together in museums to create an authentic experience for visitors.